Investigation and characterization of ultrasonically welded GF/PA6T composites. (2020) - Kalyan Kumar, R.; Omkumar, M.
Abstract: High-performance polyamides (HPPA) matrix composite meets the demanding requirement of automotive thermal management applications as a replacement to conventional metals. Effective joining of such composites are still a challenge and a better understanding of material performance upon joining are needed. This research study investigates the behavior of glass filled semi-crystalline and partially aromatic polyamide composite upon ultrasonic plastic welding. Welding process parameters were experimentally realized for a quality weld in shear type joint configuration. A weld strength of 3.1 kN was achieved. Material performance, thermal transition, degradation temperature, mass loss and morphology near welding zone were evaluated by advanced characterization techniques. A decrease in glass transition temperature (Tg ) and change in material crystallinity were observed. The morphology of welded interface reveals minimum void formation. Negligible amount of weight loss was observed after welding with a degradation temperature much higher than material melting point, suitable for high temperature applications.